2022
DOI: 10.1038/s41598-022-16593-6
|View full text |Cite
|
Sign up to set email alerts
|

Latency period of PROM at term and the risk of neonatal infectious diseases

Abstract: To find the risk of time thresholds of PROM for infectious diseases of term neonates. A multi-center prospective cohort study including pregnancies with PROM at term with a single fetus were conducted. Time thresholds of the duration from PROM to delivery were examined in 2-h increments to assess the rates of infectious neonatal diseases. 7019 pregnancies were included in the study. Neonatal pneumonia and sepsis were most frequent infectious diseases in neonates born from mother with PROM at term. Rates of ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…We then found that the risk of infection in PPROM infants is associated with the duration of PROM, which is similar to the findings in term infants [5] , [32] . To understand the underlying mechanism, the structural characterization of the gut microbiota in PPROM infants was further dissected dynamically with the duration using 12 h as a cutoff.…”
Section: Discussionsupporting
confidence: 83%
“…We then found that the risk of infection in PPROM infants is associated with the duration of PROM, which is similar to the findings in term infants [5] , [32] . To understand the underlying mechanism, the structural characterization of the gut microbiota in PPROM infants was further dissected dynamically with the duration using 12 h as a cutoff.…”
Section: Discussionsupporting
confidence: 83%